Erythrocyte-UFA (Eufa) mobility test for multiple sclerosis: implications for pathogenesis and handling of the disease - Field, E J; Joyce, G; Smith, B M (Journal of neurology, 1977)
Erythrocytes from patients with Multiple Sclerosis (MS) show a highly significant reduction in their absolute electrophoretic mobility in the presence of linoleic and arachidonic acids (LA; AA). Patients with other (destructive) neurological disease (OND) and normal subjects show an increased absolute mobility of their erythrocytes in the presence of LA and AA. About 40 per cent of blood relatives of MS patients show an intermediate type of reaction - being slowed by LA and speeded up by AA. Administration of LA (or gamma linolenate) to an MS patient for some months leads to change in the mobilities from the MS to normal type, the AA result altering first. The effect of LA and AA on the absolute mobility of RBC may thus be used as a simple laboratory test involving a long established technique and eliminating the animal and other needs of the macrophage electrophoretic mobility (MEM) test. The implications of these findings for our understanding and handling of MS are briefly discussed.